THE EXPERIENCE OF THE TEACHING TRAINING - Fernanda Barreto Mielke; Agnes Olschowsky (Universidade Federal do Paraná, 2009)
This article reports the experience of the teaching training of graduation students developed in the disciplineof Mental Health Nursing II, in the fifth period of the Nursing undergraduate program, at the Federal University of Rio Grandedo Sul. The training was developed between August and December , 2007 in a family health unit, with two family health teams.Home visits were performed for to know the reality of the people's life. The students developed a relevant work to the unit inquestion, assisting in the resolution of certain situations, providing quality care and increasing the supply of services tousers of mental health, regarding social reintegration. The experience was of great value, including various stages of educationand providing a more critical thinking about mental health and their relations with other health areas.